2001
DOI: 10.1007/s004640000339
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy in octogenarians and older patients

Abstract: Colonoscopy is safe in octogenarians and older patients. Age does not, by itself, confer an increased risk to the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 9 publications
(26 reference statements)
3
33
1
2
Order By: Relevance
“…Across all age groups, including those with advanced age, procedures were completed with similar procedural complications. Our observation confirms previous studies done in Western geriatric populations [9][10][11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Across all age groups, including those with advanced age, procedures were completed with similar procedural complications. Our observation confirms previous studies done in Western geriatric populations [9][10][11].…”
Section: Discussionsupporting
confidence: 93%
“…This rate is similar to the rate of 1.4% reported by Clarke et al [9]. The rate of colonic perforation in the very elderly patient group was 0.8%, similar to the study by Lagares-Garcia et al [11].…”
Section: Discussionsupporting
confidence: 91%
“…While some experts are against sedation due to its potential adverse events and to the acceptable tolerance to endoscopic procedures by elderly patients (12,21), several studies support safety of sedation in the geriatric population (5,18,(22)(23)(24)(25)(26). Further, it has been recently published that detection rate of neoplastic lesions (its prevalence increases as we get older) is partially depended on the use of sedation(33) so necessity for sedation in endoscopic procedures is strengthened, specially in the geriatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been proved that patients > 90 years present similar plasma propofol levels to younger controls although dose in older patients was 40% lower (18,20). Though this group of patients shows better tolerance to endoscopic procedures without sedation (18,21), several studies suggest that conscious and deep sedation are safe (5,18,(22)(23)(24)(25)(26). Moreover, some authors have suggested that the use of propofol by the endoscopy unit personnel may be efficient and safe even in elderly patients (5,(26)(27)(28)(29)(30), but the use of continuous propofol infusion in these group of patients is not reported.…”
Section: Introductionmentioning
confidence: 99%
“…The most common indications for colonoscopy are gastrointestinal bleeding, anemia, changes in bowel habits and abdominal pain. Elderly patients are more likely to have abnormal colonoscopic findings than younger patients [110][111][112] . In fact, colorectal cancer, vascular and diverticular diseases are more common among the elderly [111,112] .…”
Section: Elderly Patientsmentioning
confidence: 99%